Albatross and petrel overlap with pelagic longline fisheries in the Eastern Pacific Ocean - Daniel P. Crear; Thomas A. Clay; Ana P.B. Carneiro; Johannes H. Fischer; Igor Debski; David J. Anderson; Jill A. Awkerman; Alastair M.M. Baylis; Elizabeth A. Bell; Letizia Campioni; Paulo Catry; Tyler Clavelle; et al. (Fisheries Research, 2026)

Restoration of a Mid-Atlantic Coastal Bay Scallop Population (Argopecten irradians) - Richard A. Snyder; Rebecca T. Smith; Darian M. Kelley; Sean Fate; Robert J. Orth; Bowdoin Lusk; Christopher J. Patrick; Stacy A. Krueger-Hadfield; Jan McDowell; Fredrick C. Holbert; John C. Lewis; John P. Richardson; et al. (Estuaries and Coasts, 2026)
We have attempted to re-establish bay scallops to the Virginia, U.S.A. coastal bays and document the dynamics of the restoration effort. Bay scallops ( Argopecten irradians ) once flourished in the eelgrass ( Zostera marina ) of the Virginia coastal bays. Eelgrass wasting disease led to declines, and both eelgrass and scallops were completely lost after a 1933 hurricane. The Virginia Institute of Marine Science (VIMS) led a successful eelgrass restoration effort beginning in 1997, with eelgrass beds expanding at 204 ha per year since 2012 and covering over 4,800 ha in 2025. From 2009 to 2025, bay scallops were brought in from North Carolina, New York, and Florida to the VIMS Eastern Shore Laboratory (VIMS ESL) in Wachapreague, VA and used to raise bay scallops for restoration. Progeny were released to the eelgrass beds and held in spawning cages. Annual census data documented low and fluctuating scallop densities from 2012 to 2018. From 2019 to 2025, we have observed continued exponential growth with a current (2024–2025) specific growth rate of µ = 0.468 year − 1 and a population doubling time of 1.48 years. The carrying capacity of the system for the new Virginia bay scallop population remains unknown with the population still in the exponential growth phase. In 2025 the annual census documented an average density of 0.114 scallops m − 2 and maximum recorded local density within 50 m − 2 sampling stations of 0.52 scallops m − 2 . Aggregation within the population was anticipated as necessary for reproductive success and was observed in population data with increasing density.

A systematic literature inventory on the interaction between dietary factors and environmental chemical exposures for nervous system health outcomes - Chelsea A. Weitekamp; Caleb Watson; Ellen Hata; Kirstin Hester; Urmila P. Kodavanti; Christopher Lau; David M. Lehmann; Colette N. Miller; Rachel M. Shaffer; Fatima Soliman; Martha Powers; Francesca M. Branch (Food and Chemical Toxicology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Fate and transport of per- and polyfluoroalkyl substances (PFAS) across the groundwater-to-estuary continuum in an aqueous film forming foam (AFFF)-impacted watershed - Kevin W. Shaffer; Cheng-Shiuan Lee; Xiayan Ye; Molly Graffam; Ronald J. Paulsen; Carrie A. McDonough; Arjun K. Venkatesan; Christopher J. Gobler (Environmental Pollution, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Positive Feedback on Climate Warming by Stream Microbial Decomposers Indicated by a Global Space‐For‐Time Substitution Study - Javier Pérez; Luz Boyero; Richard G. Pearson; Mark O. Gessner; Alan Tonin; Naiara López‐Rojo; Juan Rubio‐Ríos; Francisco Correa‐Araneda; Alberto Alonso; Aydeé Cornejo; Ricardo J. Albariño; Sankarappan Anbalagan; et al. (Global Change Biology, 2025)
Decomposition of plant litter is a key ecological process in streams, whose contribution to the global carbon cycle is large relative to their extent on Earth. We examined the mechanisms underlying the temperature sensitivity (TS) of instream decomposition and forecast effects of climate warming on this process. Comparing data from 41 globally distributed sites, we assessed the TS of microbial and total decomposition using litter of nine plant species combined in six mixtures. Microbial decomposition conformed to the metabolic theory of ecology and its TS was consistently higher than that of total decomposition, which was higher than found previously. Litter quality influenced the difference between microbial and total decomposition, with total decomposition of more recalcitrant litter being more sensitive to temperature. Our projections suggest that (i) warming will enhance the microbial contribution to decomposition, increasing CO 2 outgassing and intensifying the warming trend, especially in colder regions; and (ii) riparian species composition will have a major influence on this process.

Accumulation and trophic transfer of per- and polyfluoroalkyl substances (PFAS) in estuarine organisms determined via stable isotopes - Kevin W. Shaffer; Xiayan Ye; Cheng-Shiuan Lee; Oliver N. Shipley; Carrie A. McDonough; Arjun K. Venkatesan; Christopher J. Gobler (Science of The Total Environment, 2025)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Corrigendum to “Quantifying annual spatial consistency in chick-rearing seabirds to inform important site identification” [Biol. Conserv. 281 (2023) 109994] - Martin Beal; Paulo Catry; Richard A. Phillips; Steffen Oppel; John P.Y. Arnould; Maria I. Bogdanova; Mark Bolton; Ana P.B. Carneiro; Corey Clatterbuck; Melinda Conners; Francis Daunt; Karine Delord; et al. (Biological Conservation, 2023)

Quantifying annual spatial consistency in chick-rearing seabirds to inform important site identification - Martin Beal; Paulo Catry; Richard A. Phillips; Steffen Oppel; John P.Y. Arnould; Maria I. Bogdanova; Mark Bolton; Ana P.B. Carneiro; Corey Clatterbuck; Melinda Conners; Francis Daunt; Karine Delord; et al. (Biological Conservation, 2023)

Unbound Brain-to-Plasma Partition Coefficient, Kp,uu,brain—a Game Changing Parameter for CNS Drug Discovery and Development - Irena Loryan; Andreas Reichel; Bo Feng; Christoffer Bundgaard; Christopher Shaffer; Cory Kalvass; Dallas Bednarczyk; Denise Morrison; Dominique Lesuisse; Edmund Hoppe; Georg C. Terstappen; Holger Fischer; et al. (Pharmaceutical Research, 2022)
Purpose More than 15 years have passed since the first description of the unbound brain-to-plasma partition coefficient (K p,uu,brain ) by Prof. Margareta Hammarlund-Udenaes, which was enabled by advancements in experimental methodologies including cerebral microdialysis. Since then, growing knowledge and data continue to support the notion that the unbound (free) concentration of a drug at the site of action, such as the brain, is the driving force for pharmacological responses. Towards this end, K p,uu,brain is the key parameter to obtain unbound brain concentrations from unbound plasma concentrations. Methods To understand the importance and impact of the K p,uu,brain concept in contemporary drug discovery and development, a survey has been conducted amongst major pharmaceutical companies based in Europe and the USA. Here, we present the results from this survey which consisted of 47 questions addressing: 1) Background information of the companies, 2) Implementation, 3) Application areas, 4) Methodology, 5) Impact and 6) Future perspectives. Results and conclusions From the responses, it is clear that the majority of the companies (93%) has established a common understanding across disciplines of the concept and utility of K p,uu,brain as compared to other parameters related to brain exposure. Adoption of the K p,uu,brain concept has been mainly driven by individual scientists advocating its application in the various companies rather than by a top-down approach. Remarkably, 79% of all responders describe the portfolio impact of K p,uu,brain implementation in their companies as ‘game-changing’. Although most companies (74%) consider the current toolbox for K p,uu,brain assessment and its validation satisfactory for drug discovery and early development, areas of improvement and future research to better understand human brain pharmacokinetics/pharmacodynamics translation have been identified.

“Spider Monkey Cotton”: Bridging Waiwai and Scientific Ontologies to Characterize Spider Monkey (Ateles paniscus) Filariasis in the Konashen Community Owned Conservation Area, Guyana - Christopher A. Shaffer; Marissa S. Milstein; Laramie L. Lindsey; Tiffany M. Wolf; Philip Suse; Elisha Marawanaru; Evan J. Kipp; Tyler Garwood; Dominic A. Travis; Karen A. Terio; Peter A. Larsen (International Journal of Primatology, 2022)

Machine Learning Can Assign Geologic Basin to Produced Water Samples Using Major Ion Geochemistry - Jenna L. Shelton; Aaron M. Jubb; Samuel W. Saxe; Emil D. Attanasi; Alexei V. Milkov; Mark Engle; Philip A. Freeman; Christopher A. Shaffer; Madalyn S. Blondes (Natural Resources Research, 2021)
Understanding the geochemistry of waters produced during petroleum extraction is essential to informing the best treatment and reuse options, which can potentially be optimized for a given geologic basin. Here, we used the US Geological Survey’s National Produced Waters Geochemical Database (PWGD) to determine if major ion chemistry could be used to classify accurately a produced water sample to a given geologic basin based on similarities to a given training dataset. Two datasets were derived from the PWGD: one with seven features but more samples (PWGD7), and another with nine features but fewer samples (PWGD9). The seven-feature dataset, prior to randomly generating a training and testing (i.e., validation) dataset, had 58,541 samples, 20 basins, and was classified based on total dissolved solids (TDS), bicarbonate (HCO 3 ), Ca, Na, Cl, Mg, and sulfate (SO 4 ). The nine-feature dataset, prior to randomly splitting into a training and testing (i.e., validation) dataset, contained 33,271 samples, 19 basins, and was classified based on TDS, HCO 3 , Ca, Na, Cl, Mg, SO 4 , pH, and specific gravity. Three supervised machine learning algorithms—Random Forest, k-Nearest Neighbors, and Naïve Bayes—were used to develop multi-class classification models to predict a basin of origin for produced waters using major ion chemistry. After training, the models were tested on three different datasets: Validation7, Validation9, and one based on data absent from the PWGD. Prediction accuracies across the models ranged from 23.5 to 73.5% when tested on the two PWGD-based datasets. A model using the Random Forest algorithm predicted most accurately compared to all other models tested. The models generally predicted basin of origin more accurately on the PWGD7-based dataset than on the PWGD9-based dataset. An additional dataset, which contained data not in the PWGD, was used to test the most accurate model; results suggest that some basins may lack geochemical diversity or may not be well described, while others may be geochemically diverse or are well described. A compelling result of this work is that a produced water basin of origin can be determined using major ions alone and, therefore, deep basinal fluid compositions may not be as variable within a given basin as previously thought. Applications include predicting the geochemistry of produced fluid prior to drilling at different intervals and assigning historical produced water data to a producing basin.

Roadside monkeys: anthropogenic effects on moor macaque (Macaca maura) ranging behavior in Bantimurung Bulusaraung National Park, Sulawesi, Indonesia - Erin P. Riley; Christopher A. Shaffer; Joshua S. Trinidad; Kristen S. Morrow; Cristina Sagnotti; Monica Carosi; Putu Oka Ngakan (Primates, 2021)

Integrating Ethnography and Hunting Sustainability Modeling for Primate Conservation in an Indigenous Reserve in Guyana - Christopher A. Shaffer; Marissa S. Milstein; Phillip Suse; Elisha Marawanaru; Charakura Yukuma; Tiffany M. Wolf; Dominic A. Travis (International Journal of Primatology, 2018)

Insights from mathematical modeling for convection-enhanced intraputamenal delivery of GDNF - Elena Belova; Christopher L. Shaffer; Patrick E. Trapa (Medical & Biological Engineering & Computing, 2017)

Experimental and archaeological investigations of backed microlith function among Mid-to-Late Holocene herders in southwestern Kenya - Steven T. Goldstein; Christopher M. Shaffer (Archaeological and Anthropological Sciences, 2017)

Sustainability and comanagement of subsistence hunting in an indigenous reserve in Guyana - Christopher A. Shaffer; Marissa S. Milstein; Charakura Yukuma; Elisha Marawanaru; Phillip Suse (Conservation Biology, 2017)
Although hunting is a key component of subsistence strategies of many Amazonians, it is also one of the greatest threats to wildlife. Because indigenous reserves comprise over 20% of Amazonia, effective conservation often requires that conservation professionals work closely with indigenous groups to manage resource use. We used hunter‐generated harvesting data in spatially explicit biodemographic models to assess the sustainability of subsistence hunting of indigenous Waiwai in Guyana. We collected data through a hunter self‐monitoring program, systematic follows of hunters, and semistructured interviews. We used these data to predict future densities of 2 indicator species, spider monkeys ( Ateles paniscus ) and bearded sakis ( Chiropotes sagulatus ), under different scenarios of human population expansion and changing hunting technology. We used encounter rates from transect surveys and hunter catch‐per‐unit effort (CPUE) to validate model predictions. Paca ( Cuniculus paca ) (198 /year), Currosaw ( Crax alector ) (168), and spider monkey (117) were the most frequently harvested species. Predicted densities of spider monkeys were statistically indistinguishable from empirically derived transect data (Kolmogorov–Smirnov D = 0.67, p = 0.759) and CPUE ( D = 0.32, p = 1.000), demonstrating the robustness of model predictions. Ateles paniscus and C. sagulatus were predicted to be extirpated from

Delayed life history effects, multilevel selection, and evolutionary trade‐offs in the California tiger salamander - Christopher A. Searcy; Levi N. Gray; Peter C. Trenham; H. Bradley Shaffer (Ecology, 2014)
Delayed life history effects (DLHEs) occur when fitness in one life stage affects fitness in subsequent life stages. Given their biphasic life cycle, pond‐breeding amphibians provide a natural system for studying DLHEs, although these effects are not restricted to species with biphasic life histories. In this study, we used multiple mark–recapture techniques enabled by a large trapping array to monitor components of fitness and resulting DLHEs in a population of the endangered California tiger salamander ( Ambystoma californiense ). We found that DLHEs are prominent across all life stage transitions and that there is variation in whether selection acts primarily at the individual or cohort level. We also demonstrated that there is more than an order of magnitude variation in mean cohort fitness, providing tremendous variation for DLHEs to act upon. We documented an evolutionary trade‐off between mass at emergence and date of emergence, which may play a role in maintaining the variation in mass (fitness) at emergence. A literature review revealed that such high levels of intercohort variation occur in many other pond‐breeding amphibians, and that appropriately documenting the magnitude of intercohort variation requires long‐term studies (roughly two population turnovers). Given the profound effect that DLHEs can have on population dynamics, quantifying intercohort variation in mean fitness and the level(s) at which selection acts will be very important for developing accurate models of population dynamics. In general, when developing models of population dynamics, more attention should be paid to variation in mean fitness and not just variation in total numbers.

Activity Patterns, Intergroup Encounters, and Male Affiliation in Free-Ranging Bearded Sakis (Chiropotes sagulatus) - Christopher A. Shaffer (International Journal of Primatology, 2013)

Ecological Correlates of Ranging Behavior in Bearded Sakis (Chiropotes sagulatus) in a Continuous Forest in Guyana - Christopher A. Shaffer (International Journal of Primatology, 2013)

Calculating Biologically Accurate Mitigation Credits: Insights from the California Tiger Salamander - CHRISTOPHER A. SEARCY; H. BRADLEY SHAFFER (Conservation Biology, 2008)
Current conservation mitigation plans often fail to ensure full in‐kind habitat replacement for endangered species, which suggests the need for improved methods for calculating mitigation credits. A simple, yet biologically meaningful method for calculating mitigation credits would be to let the number of mitigation credits assigned to a parcel of land scale with the reproductive value of the individuals occupying that parcel. This can be accomplished by dividing the population into 2 or more subdivisions with different reproductive values, calculating the densities of these subdivisions as a function of one or more habitat parameters, and then forming a weighted sum of these densities such that each density distribution is weighted by the reproductive value of its respective subdivision of the population. This weighted sum is the density distribution of reproductive value, and by integrating it over a particular parcel, one can determine the mitigation value of that parcel. We carried out this procedure for a population of California tiger salamanders ( Ambystoma californiense ), with distance from breeding site as our habitat parameter and the 3 visually identifiable age classes (adults, juveniles, and metamorphs) as our population subdivisions. This led to a density distribution of reproductive value that decreased exponentially with increasing distance from a breeding site. Mitigation strategies derived from this function will be more likely to ensure the persistence of California tiger salamander populations than current approaches, which assign all land within 1.6 km of a breeding site the same mitigation value. Use of the density distribution of reproductive value as a basis for mitigation plans is a procedure that can be applied to all endangered species, and it should improve the quality of mitigation decisions.

Haploinsufficiency of PAX9 is associated with autosomal dominant hypodontia - Parimal Das; David W. Stockton; Christopher Bauer; Lisa G. Shaffer; Rena N. D’Souza; Timothy J. Wright; Pragna I. Patel (Human Genetics, 2002)